2012
DOI: 10.1890/es11-00298.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial bottom‐up controls on fire likelihood vary across western North America

Abstract: Abstract. The unique nature of landscapes has challenged our ability to make generalizations about the effects of bottom-up controls on fire regimes. For four geographically distinct fire-prone landscapes in western North America, we used a consistent simulation approach to quantify the influence of three key bottom-up factors, ignitions, fuels, and topography, on spatial patterns of fire likelihood. We first developed working hypotheses predicting the influence of each factor based on its spatial structure (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 67 publications
1
61
1
1
Order By: Relevance
“…The interaction of top-down and bottom-up factors governs forest fire regimes over a range of spatial and temporal scales. The bottom-up controls usually act at fine scales by regulating fire physics and behavior [8]. For instance, fire propagation is mainly controlled by weather, local terrain plus fuel load, moisture content, and fuel continuity.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of top-down and bottom-up factors governs forest fire regimes over a range of spatial and temporal scales. The bottom-up controls usually act at fine scales by regulating fire physics and behavior [8]. For instance, fire propagation is mainly controlled by weather, local terrain plus fuel load, moisture content, and fuel continuity.…”
Section: Introductionmentioning
confidence: 99%
“…Fire weather is considered a top-down control as its impacts on fire are described at a broad spatial extent. Topography and fuel conditions are usually considered bottom-up controls as their impacts on fire activity are spatially more variable (Cyr et al, 2007;Parks et al, 2012). It has been demonstrated that the relationship between fire activity and patterns of fire-induced ecological consequences could exhibit nonlinearities across a gradient of spatial scales due to interactions between top-down and bottom-up controls (Peters et al, 2004(Peters et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In light of increasing fire activity and ever-growing fire-suppression expenditures (Calkin et al 2015), it is imperative that we understand how wildland fire influences subsequent disturbance processes. In addition, improved knowledge of what factors (i.e., spatial and temporal variation in climate) enhance or constrain wildland fire's self-limiting effect could also be useful to those who model fire likelihood and risk across large landscapes (Finney et al 2011, Parisien et al 2011, Parks et al 2012) and potentially inform efforts to predict fire activity under a warming climate (Batllori et al 2013, McKenzie and Littell 2017, Parks et al 2017. Miller 2003, North et al 2012, Hessburg et al 2015.…”
Section: Introductionmentioning
confidence: 99%